Correlation Between Arm Muscle Power and Badminton Smash Skill (Department of Physical Education, Sport, Health and Recreation, 2021)
Based on theoretical studies, the variable arm muscle power is an important factor of physical condition in supporting badminton smash skills. This study aims to determine the correlation between arm muscle power and badminton smash skills. This research uses a quantitative approach with correlational research type. The research sample consisted of 73 people who were selected from physical Serambi Mekkah University, Banda Aceh. The research instruments used for each varibale were: arm muscle power using the shot put test instrument, while for badminton smash skills using a process and result test developed by the author himself, the data analysis stages consisted of calculating the mean, standard deviation.. The stages of data analysis carried out were the calculation of the average, standard deviation, determination of the t score, calculation of the correlation and the t test to determine the significance of the correlation between variables. Based on the analysis of research data, The correlation between arm muscle power and badminton smash skills is (r = 0.88. which means that there is a significant correlation between arm muscle power and badminton smash skills. Based on the calculation of the coefficient of determination, it was also found that arm muscle power contributed 78.68% to badminton smash skills.